A review of guidelines, recommendations, and framework of men's preconception care. Issue 4 (29th November 2022) - Rabiei, Zeinab; Shariati, Mohammad; Mogharabian, Naser; Tahmasebi, Rahim; Ghiasi, Ashraf; Motaghi, Zahra
Abstract : The focus of men's health is within the context of preconception health and primary care, which involves a new method of engaging men's attention to their preconception and general health. The aim of this review research is to offer health care practitioners a complete framework for men's preconception care. From 2000 to October 2021, researchers examined electronic databases such as Web of Science, PubMed, Scopus, ScienceDirect, ProQuest, Cochrane, SAGE, Springer, UpToDate, and Google Scholar for published papers on men's preconception care. Two independent authors assessed the quality of the included studies using techniques suitable for this type of investigation. Only 14 of the 835 studies that were found in the original search matched the inclusion criteria. Individual responsibility across the life span (evaluation of reproductive life plan, acquiring information about contraception) and risk assessment (age, medical and surgical history, medications, family history and genetic risks, social history, sexual health assessment, physical examination, laboratory testing, mental health, and intimate partner violence) are the two main topics of preconception care in men according to a review of studies. Our findings clearly demonstrated the critical components of a comprehensive preconception care approach for men. Therefore, preconception care for men remains a developing concept. Further research is required to develop standards for evaluating males during the preconception period.